Copyright in cyberspace media - DESANTES GUANTER, JOSÉ MARÍA (Investigación Bibliotecológica. Archivonomía, bibliotecología e información, 1998)
THE ARTICLE TACKLES THE JURIDICAL AND LEGAL PROBLEM THAT THE SEARCH FOR SOLUTIONS WITH RESPECT TO SO-CALLED COPYRIGHT IS BEGINNING TO GENERATE. THE SUBJECT HAS UNDERGONE SUBSTANTIAL CHANGES WITH THE APPEARANCE OF CYBERSPACE WHICH, AMONG OTHER THINGS, SUPPOSES A CONCENTRATION OF MEDIA THAT PERMIT MORE COMPLEX MESSAGES , WHICH AT THE SAME TIME PRESENTS NEW PROBLEMS WITH RESPECT TO THE ATTRIBUTION OF COPYRIGHT OWNERSHIP. WHAT TO DO, FOR EXAMPLE, WITH CERTAIN OBJECTS THAT CAN ALSO BE PROTECTED BY COPYRIGHT, SUCH AS THE SPECIAL STRUCTURE OF EXPRESSION, INDEXING THESAURUS, THE SPECIFIC COMPUTER PROGRAM FOR ELABORATING THE STRUCTURE AND THE CONSEQUENT USE OF WINDOWS, BACKGROUNDS, ICONS, AND CONTROL PANELS THAT MAKE UP EACH ONE OF THESE PROGRAMS? ONCE